PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DALAM KEMAMPUAN MENULIS PUISI PADA PESERTA DIDIK KELAS X SMK NU KAPETAKAN KABUPATEN CIREBON (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem examined in this study is whether the learning outcomes of students who are taught using the Example Non-Example learning model differ from those who are taught using conventional learning methods. This study aims to determine whether there is a difference in students’ learning outcomes in poetry writing between those who apply the Example Non-Example model and those who use conventional learning models. The sample of this study was taken from two Grade X TBSM classes at SMK NU Kapetakan. Data collection was carried out using pretest and posttest results of students’ learning outcomes in poetry writing in the form of written works. The data analysis technique used descriptive statistics, as follows: (1) the learning outcomes of students in poetry writing who applied the Example Non-Example model (experimental class) achieved an average score of 84.44 with a standard deviation of 5.261; (2) the learning outcomes of students who applied the conventional learning model (control class) achieved an average score of 61 with a standard deviation of 5.568. The results show that students taught using the Example Non-Example model have higher learning outcomes compared to those taught using conventional learning methods.